AGRICULTURAL MARKETING IN INDIA DEFECTS AND THEIR REMEDIAL MEASURES - Yashwanth, J (Global journal of Business and Integral Security, 2023)
India is a country in which majority of people depends on agriculture sector for their livelihood and farmers are considered as the backbone of the country. Even though India is an agrarian economy, agricultural marketing is the major concern which farmers are facing in the country. The problems for farmers in agricultural marketing starts from crop selection and ends with executing the trade for the same. Without having knowledge on demand and supply in market farmers randomly picks up the crop to be grown which affects the entire supply chain system. During harvest they have to pay huge labor costs for harvest and also high transportation charges to take the produce to the markets for sale. In markets they have to pay 10% commission to the middleman for executing the trade. These all charges cuts down the farmer’s revenue and profits and they are not even getting the return on investments which makes them to migrate into other sectors for their livelihood. Also consumers are facing many problems due to this traditional system of Agricultural marketing such as 1. Quality less produce, 2. High prices for the produce, 3. Lack of hygiene, 4. Lack of traceability. Even though consumers are paying higher prices for the produce, they are not getting quality and hygienic produce which damages both health and wealth of the consumers. In order to solve these problems several concepts were employed by government as well as different private institutions like evezon, dFarm, udaan, e-Nam etc.… since few years. This paper gives the detailed information about those defects and remedial measures in the agriculture marketing system in India.